The right of peoples to self-determination - Bursać Slobodanka (Međunarodni Problemi, 2010)
Applying as a criterion the area of achievement the author divides the right of peoples to self-determination to external and internal, while it is divided to political, economic and cultural when applying the sphere of social life as a criterion. While the right to self-determination undoubtedly belongs to peoples the recognition of this right to other groups, such as indigenous peoples and minorities requires a deeper analysis. The author defines the concept of holders of the right to self-determination that necessarily includes a territorial element. By all this, she analyses two concepts that are related to this right - uti possidetis principle and safeguard clause.